Concepções de leitura e de leitores em pride and prejudice e sense and sensibility de Jane Austen - Campos, Priscila da Silva (2017)
Jane Austen is an important English writer at the turn of the eighteenth into the nineteenth century. She is praised for her vivid description of the English society, the development of important narrative techniques, and the deep psychological treatment of her characters. In her six novels, Austen discusses social and literary issues that were important in her day. Therefore, Austen’s fiction has been the subject of a wealth of critical studies. Nonetheless, there is an aspect of her fiction that has not been sufficiently studied yet, namely, the notions of reading and readers. Two novels are especially meaningful to discuss this issue: Pride and Prejudice (1813) and Sense and Sensibility (1811). Thus, this study aims to identify and discuss the notions of reading and readers in both novels. The characters/readers of each novel are analyzed with regards to their individual attitude as readers of fictional and non-fictional texts and of the circumstances they live. The analysis enables us to discuss the notions of reading and readers that the author defends or criticizes. We can affirm that this topic was not only an important subject for Jane Austen and the English society, but also an internalized and structuring aspect of her novels. The reading and re-reading process experienced by Austen’s characters allows for their psychological depth once the narrative voice penetrates into the characters’ consciousness or moves away from them in order to comment on and evaluate their attitude as readers. In both novels, the author discusses the process of internalization and subjectivation of reading. Therefore, through the different notions of reading and readers present in Pride and Prejudice and Sense and Sensibility, Austen not only defends the importance of reading and re-reading for the reader’s intellectual and emotional maturity (an issue that is still topical), but also opens up new perspectives for the novel as a literary genre.